Novel dynamic impairment-aware algorithm for modulation, core, and spectrum assignment in SDM-EONs - Lacerda Júnior, J.; Cartaxo, A.; Soares, A. C. B. (Optical Switching and Networking, 2024)
Space-division multiplexed elastic optical networks (SDM-EONs) utilizing multi-core fiber (MCF) have been considered to address the growing traffic demand in transport networks. The quality of transmission (QoT) of MCF-based SDM-EONs is affected by inter-core and intra-core physical layer impairments (PLIs). This paper proposes an inter-core crosstalk-aware and intra-core impairment-aware algorithm for modulation, core, and spectrum assignment (CIA-MCSA) in MCF-based SDM-EONs. The CIA-MCSA considers PLI estimation in a dynamic traffic scenario and allocates new lightpaths using strategies to avoid blocking by insufficient QoT of the new lightpath and of already active lightpaths. Using numerical simulation, the performance of the CIA-MCSA is compared with five algorithms proposed by other authors, considering two distinct network topologies, heterogeneous traffic demands, and different levels of inter-core crosstalk. The results show that, when compared with the most competitive of the other algorithms, (i) CIA-MCSA achieves an average reduction of the request blocking probability by at least 33.87%; (ii) CIA-MCSA achieves an average reduction of the bandwidth blocking probability by at least 20.74%; and (iii) CIA-MCSA increases the network spectrum utilization by at least 3.04%.